2011
DOI: 10.1159/000335066
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mild to Moderate Kidney Dysfunction with Coronary Artery Calcification in Patients with Suspected Coronary Artery Disease

Abstract: Objectives: To report the association between kidney dysfunction and coronary artery calcification (CAC) score (CACS) among patients with clinically suspected coronary artery disease (CAD). Methods: We prospectively included 1,572 consecutive patients with clinically suspected CAD who underwent ECG-gated cardiac CT scans using 64-multidetector row computed tomography. CACS was quantified using a previously described method. Renal function was assessed by the estimated glomerular filtration rate (eGFR). Ordinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Kiyosue et al [ 39 ] investigated the association of severity of CAD with CKD and revealed that the number of stenotic coronary arteries were higher in the CKD group. Our previous study [ 40 ] demonstrated that mild to moderate renal kidney dysfunction was an independent predictor of CAC score in patients with clinically suspected CAD. Our recent study retrospectively investigated the relationship between kidney function and angiographically derived SXscore and suggested that kidney function estimated by GFR based on serum creatininebased equations was an independent predictor of SXscore in patients with established CAD.…”
mentioning
confidence: 93%
“…Kiyosue et al [ 39 ] investigated the association of severity of CAD with CKD and revealed that the number of stenotic coronary arteries were higher in the CKD group. Our previous study [ 40 ] demonstrated that mild to moderate renal kidney dysfunction was an independent predictor of CAC score in patients with clinically suspected CAD. Our recent study retrospectively investigated the relationship between kidney function and angiographically derived SXscore and suggested that kidney function estimated by GFR based on serum creatininebased equations was an independent predictor of SXscore in patients with established CAD.…”
mentioning
confidence: 93%
“…Cao et al [2] presents the latest evidence that we as physicians must more aggressively treat patients with CKD to meet cardiovascular treatment goals.…”
mentioning
confidence: 99%
“…It is becoming increasingly evident that patients with CKD are more likely to die of cardiovascular disease than their kidney dysfunction [1] . The latest study from Cao et al [2] in this issue of Cardiology correlating CKD and cardiovascular disease is based on one of the largest cohorts to date. It is the first study showing that kidney dysfunction is an independent predictor of coronary artery calcium (CAC) scores in patients with clinically suspected coronary artery disease (CAD).…”
mentioning
confidence: 99%
See 2 more Smart Citations